Application of 30° Upper Extremity Elevation for Edema Reduction in Patients with Hypervolemia: A Case Study - Sandra Mariska Sukma; Maria Komariah; Nita Fitria (Universitas Dehasen Bengkulu, 2026)
Patients with Diabetes Mellitus (DM) and hypertension are at high risk of impaired renal function and fluid retention, leading to hypervolemia and peripheral edema. This condition reduces comfort and physical function. Non-pharmacological interventions, such as limb elevation, are important nursing actions to reduce interstitial fluid accumulation. This case study aimed to analyze the effect of 30° hand elevation on reducing edema grade in a patient with hypervolemia due to chronic disease. A qualitative descriptive case study design was used with a single subject (Mrs. E, 53 years old) in the inpatient ward of RSUD Welas Asih. The intervention was performed for 15 minutes, four times daily, over three days, alongside collaborative therapy including furosemide infusion and fluid restriction. Results showed a progressive reduction in edema from grade 4 to grade 2 by the third day, indicating improved venous and lymphatic return. These findings suggest that 30° hand elevation is a simple, safe, and effective independent nursing intervention to reduce upper extremity edema in hypervolemic patients and can be integrated with pharmacological therapy under proper supervision.